Effect of extrusion on physicochemical and functional properties of cladode flour from Opuntia cochenillifera and Opuntia ficus-indica - Denhy Jaquelinee Pérez-Viveros; Luis Díaz-Batalla; Ricardo Omar Navarro-Cortez; Heidi María Palma-Rodríguez; Juan Pablo Hernández-Uribe (Applied Food Research)
In this study, the physicochemical and functional properties of flours obtained from mature cladodes of two nopal species, Opuntia cochenillifera (OC) and Opuntia ficus indica (OF), subjected to different extrusion conditions, varying moisture (20 % and 26 %) and temperature levels (120 °C, 140 °C and 160 °C) were evaluated. The results showed significant differences in chemical composition, physical, functional and phytochemical properties between the two species. OC had a higher ash and ether extract content (29.27 % and 1.28 % respectively), while OF had more protein and carbohydrates (7.83 and 55.31 % respectively). The expansion index was higher (1.06 – 1.27) in OF, especially under high temperature extrusion and low moisture conditions. Bulk density decreased with increasing extrusion temperature, and color was significantly altered by temperature and moisture, with greater changes observed in OF. Functional properties such as oil absorption capacity, water absorption capacity, and water solubility index, were significantly affected by the extrusion process in both species of nopal. In terms of dietary fiber, extrusion increased (4.99 to 10.38 %) the soluble fiber content and decreased (36.91 to 32.30 %) the insoluble fiber content in both species. However, OC had a higher percentage of soluble and total dietary fiber. Phenolic compounds, flavonoids and antioxidant activity were significantly affected by the extrusion process in most treatments, although some maintained or improved these properties. These results highlight the influence of species and extrusion conditions on the properties of nopal flours, providing valuable information for the development of nopal-enriched food products, thereby optimizing their nutritional and technological properties.